Self-healable, recyclable, mechanically tough transparent polysiloxane elastomers based on dynamic microphase separation for flexible sensor. (10th December 2021) - Zhou, Xinqin; Gong, Zhou; Fan, Jianfeng; Chen, Yukun
Abstract: As yet, self-healable and recyclable polysiloxane elastomers are very meaningful for sustainable development. However, the preparation of polysiloxane elastomers integrated with excellent mechanical properties and high self-healing efficiency is itself a counter-balance between each other. Here we report the design and synthesis of a novel polysiloxane elastomer through dynamic microphase separation to address this conundrum. The hydrogen bonding generates between soft block and hard block can enable strong microphase separation, which provides this series of elastomers (PMD) with excellent mechanical properties. It is tunable that the tensile strength is 1.89–3.33 MPa, the stretchability is 347–1722%, the extreme fracture toughness is 28.6 MJ/m3, which is very prominent compared to previous reports. The locked disulfide bonds can be easily activated to make it highly dynamic above the T g, endowing the elastomers with excellent self-healing ability and recyclability. Taking advantages of the merits of PMD, a "sandwich-structure" flexible sensor device, cutting and healing just like building blocks, is designed that can be utilized for detecting human motions. It is expected to realize the customized construction of wearable electronic devices. Graphical abstract: Image 1 Highlights: A self-healable, recyclable, tough transparent polysiloxane elastomer was prepared. The microphase separation structure improved the mechanical properties. The dynamic feature of hard phases endowed the elastomer with excellent self-healing ability. A "sandwich-structure" device was designed that can be applied for flexible sensor.